Quality Standards in Upper Gastrointestinal Endoscopy: Can Deep Sedation Influence It? - Correia,Catarina (2024)
Abstract Introduction: According to the guideline published by ESGE/UEG, a high-quality esophagogastroduodenoscopy (EGD) implies the application of some criteria that enable better healthcare outcomes. Although intra-procedural performance measures are dependent on patient factors, there is no reference to sedation practices in the guideline mentioned above. Objective: This study aimed to evaluate whether deep sedation influences EGD performance measures established by ESGE/UEG. Methods: This was a cross-sectional study, with a prospective enrollment, that considered for inclusion consecutive patients referred for EGD. Two questionnaires were used to assess performance measures and patient satisfaction after EGD. Results: Sedation had a statistically significant impact on most quality indicators, including complete examination (77.2% without sedation vs. 97.8% with sedation), inspection time (6.17 ± 3.45 vs. 8.39 ±2.67 min), photodocumentation (78% vs. 97.8%), biopsies (39.3% vs. 60.7%), and patient satisfaction (5.42 ± 2.93 vs. 9.1 ± 1.19). The main reason for an incomplete procedure was patient intolerance (82.6%). Discussion: Deep sedation of patients submitted to EGD proved to be a determinant in the applicability of the ESGE/UEG quality indicators. Patient intolerance was eliminated in the group with sedation, enhancing procedure completeness, adequate pathology identification, management, and consequently, the effectiveness of the exam. Conclusion: Sedation administration should be considered in patients undergoing EGD since it ensures a high-quality procedure.